Glycaemic response of mixed meals with various portions of Green Mustard leaves (Sawi) and their effects on perceived appetite and satiety - Wen, Sally Tan Yen; Ramlah George @ Mohd. Rosli (UniSE Press, 2024)
Vegetables, a key source of dietary fibre in the diet, can influence the glycaemic response of a meal, reduce appetite and increase satiety. We investigated the effects of mixed meals with various portions of vegetables (white rice, chicken breast and green mustard leaves (40 g, 80 g,120 g)) on postprandial blood glucose and perceived appetite and satiety. Glycaemic response of three test meals was measured using established methods (n=11). The test meals were not significantly different (repeated measures ANOVA; p>0.05) in glycaemic response (iAUC) but differed in their Visual Analogue Scale (VAS) ratings for perceived appetite and satiety (Friedman’s test; p<0.05). The findings suggest that meals containing larger portions of vegetables may not substantially reduce postprandial blood glucose levels but may reduce perceived appetite and increase satiety. Further research is required to confirm these findings.